Vacuum furnace equipment for quantitative determination of trapped gases in castings - Hernández-Ortega, J. J.; Zamora, R.; Faura, F.; López, J. (Revista de Metalurgia, 2009)
Parts manufactured with casting processes may trap substantial quantities of gas, which could harm the mechanical properties of the manufactured parts. In this work, a vacuum melting device manufactured to measure trapped gas in castings is described. Adjustment correlations, which accurately calculate trapped gas quantity as a function of the pressure increments measured by the vacuum equipment, are obtained. Finally, as an application of the equipment, we present the results obtained for several parts manufactured using a pressure die casting machine. It is expected that the vacuum melting device will be useful to optimize the operating conditions which reduce the trapped gas in casting processes.